HUBUNGAN STATUS GIZI DENGAN PNEUMONIA BALITA DI PUSKESMAS UMBAN SARI PEKANBARU TAHUN 2016 - Piliang, Nelfi Sarlis; Filda, Mutya (Jurnal Endurance, 2018)
According to the health ministry Indonesia, pneumonia is an cause death to two infants after diarrhea. Pneumonia is an acute infection of the respiratory system that has symptoms cough, fever and shortness of breath. This research aims to determine the relationship of nutritional status with the incidence of pneumonia in toddlers in health center Umban Sari Pekanbaru year 2016. This type  of research is quantitative  with correlation analysis. Research design cross sectional. Population in this research is population of all under five working  area  of  Puskesmas Umban Sari Pekanbaru year 2016 in November to December. Sampling technique sampel use Simple Random Sampling with the number of samples 187 people. It is hoped that this research can beused as input for health workers, especially midwives in improving health service for children, by way of providing education to mothers who have children under five about the provision of nutritional in take to their children and identification risk factor that occur when a poorly metabolized intake leads to infection. Menurut Kementerian Kesehatan, pneumonia merupakan penyebab kematian kedua balita setelah diare. Pneumonia merupakan infeksi akut pada sistem pernafasan yang mempunyai gejala batuk, demam dan sesak nafas. Penelitian ini bertujuan untuk mengetahui hubungan status gizi dengan kejadian pneumonia pada balita di Puskesmas Umban Sari Pekanbaru Tahun 2016. Jenis penelitian ini adalah kuantitatif dengan analisis korelasi. Desain penelitian cross sectional. Populasi dalam penelitian ini adalah populasi seluruh balita di wilayah Kerja Puskesmas Umban Sari Pekanbaru Tahun 2016 pada bulan November sampai Desember. Teknik pengambilan sampel menggunakan Simple Random Sampling dengan jumlah sampel 187 orang. Adapun hasil bivariat dari uji Chi-square menunjukkan hasil bahwa terdapat hubungan yang bermakna antara status gizi dengan kejadian pneumonia pada balita. Diharapkan penelitian ini dapat dijadikan masukkan bagi tenaga kesehatan khususnya bidan dalam meningkatkan pelayanan kesehatan bagi balita.